Pengukuran Focus Factor Tim Scrum pada Proyek Perangkat Lunak Skala Kecil - Nuraminah, Ahlijati (JURNAL UNITEK, 2025)
Scrum, an Agile methodology widely employed in software development, emphasizes collaboration, adaptability, and delivering high-value products. While Velocity is commonly used to measure team performance, it may not provide a comprehensive picture due to factors like the number of developers and working days considered. To address this, the Focus Factor is introduced, accounting for these factors and providing a more nuanced evaluation of team focus and concentration during each Sprint. This research analyzes a Scrum Team's performance using the Focus Factor in a small-scale software project, aiming to understand its advantages in enhancing software development efficiency. The method involves Scrum initiation, data collection, Focus Factor calculation, analysis, and evaluation. The results from seven Sprints indicate varying team performances, with some achieving high Focus Factor values, reflecting efficient focus, while others exhibit lower performance. In conclusion, the Focus Factor proves valuable in assessing team performance, offering insights into areas of improvement. Future research can explore its application in larger projects to evaluate teams' ability to maintain high focus and productivity amidst more extensive user stories